Electric Load Controller Untuk Pembangkit Listrik Tenaga Mikro Hidro - Ardianto , Mukhlas; Pratilastiarso, Joke; Permatasari , Prima Dewi (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2019)
In implementation, PLTMH utilizes different head heights so that the potential energy of water is converted into mechanical energy to turn turbines. Then the generator will convert mechanical energy from the turbine shaft rotation into electrical energy. In the operation of PLTMH, fluctuating loads cause unstable frequencies and voltages that can damage electrical equipment and cause overspeed generators when the load is very low. To regulate fluctuating loads on modern PLTMH using ELC (Electric Load Controller). The working principle of the ELC is to control the load which aims to balance the power generated by the generator with the power used by consumers. The results of the simulation conducted by a generator with 30 VA power require an excitation voltage of 52.2 V dc, the dc voltage of the buck converter is capable of producing an output of 52.2 V with a duty cycle value of 0.725%. Changes in consumer loads cause the value of the generator voltage to increase, namely loading from a scale of 11-30 KW with a voltage reading of 220-235 V line-neutral. The decrease in consumer load results in the power transferred to the ballast load being greater, namely alpha angle variation from 0o - 180o. A decrease in consumer load from a scale of 11-30 KW results in the power being transferred to ballast loads from 0 KW - 30 KW. ELC is able to maintain line-neutral voltage on the 220 V set point and has 100% accuracy. The ELC simulation results are able to maintain a 220 V set point voltage with a power capacity generated by a 30 VA generator.